Sporadic Lymphangioleiomyomatosis Disease: A Case Report - Yousef Nikmanesh; Mansoureh Shokripour; Maral Mokhtari; Mahdi Khazayi; Ahmad Monabati; Ramin Rezayi; Mehrzad Bahtouee (Iranian Journal of Medical Sciences, 2023)
Pulmonary Lymphangioleiomyomatosis (LAM) is a rare disease of the lung and lymphatic system that primarily affects women of childbearing age. LAM is a progressive disease with a terrible prognosis, which worsens over time and is extremely difficult to treat. In this study, we discuss the case of a 31-year-old woman with LAM who was initially misdiagnosed with leiomyoma and the way that led to a true diagnosis and effective treatment. Following a precise diagnosis based on comprehensive clinical data and particular immunohistochemical tests, sirolimus treatment was initiated, and the patient entirely responded to the treatment. This case report demonstrated that LAM is an uncommon condition that is challenging to diagnose, which causes its treatment to be delayed.